Menopause and “leaky gut”: implications for midlife women’s health - Brandilyn A. Peters (Journal of Clinical Investigation, 2026)
Menopause may have important consequences for gut barrier health. The roles of estradiol and progesterone in immune and mucosal barrier homeostasis have been well studied in the female reproductive tract. However, few human studies have described these hormones’ corresponding regulation in the gastrointestinal tract or how the menopausal transition affects gut barrier integrity. In this issue of the JCI , Shieh et al. report that markers of gut epithelial barrier dysfunction and microbial translocation–related immune activation increased across the menopause transition in a longitudinal study of healthy women. These findings suggest that ovarian aging may contribute to gut barrier dysfunction in midlife women and highlight new questions about clinical consequences and potential interventions.